Diagnoza potencjału rozwojowego pracowników - Smolbik-Jęczmień, Alicja (Assessment of Development Potential of Employees, 2008)
The purpose of this study is to present some selected methods of assessment of development potential of employees and their impact on optimal usage of the Staff. Furthermore, basic errors in evaluation of development potential of employees along with their conseąuences were indicated. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 24, s. 204-213